An Equivocal Final Link – Quantitative Determination of the Thermodynamic Efficiency of ATP Hydrolysis – Sullies the Chain of Electric, Ionic, Mechanical and Metabolic Steps Underlying Cardiac Contraction - Barclay, Christopher John; Loiselle, Denis Scott (Frontiers in Physiology, 2020)
Each beat of the heart completes the final step in a sequence of events commencing with electrical excitation-triggered release of Ca2+ from the sarcoplasmic reticulum which, in turn, triggers ATP-hydrolysis-dependent mechanical contraction. Given that Thermodynamics is inherently detail-independent, the heart can be thus be viewed as a mechanical pump - the generator of pressure that drives blood through the systemic and pulmonary circulations. The beat-to-beat pressure-volume work (W) of the heart is relatively straightforward to measure experimentally. Given an ability to measure, simultaneously, the accompanying heat production or oxygen consumption, it is trivial to calculate the mechanical efficiency:  = W/(dH where dH is the change of enthalpy: (W + Q), Q representing the accompanying production of heat. But it is much less straightforward to measure the thermodynamic efficiency: 𝜂 = W/dGATP, where dGATP signifies the Gibbs Free Energy of ATP hydrolysis. The difficulty arises because of uncertain quantification of the substrate-dependent yield of ATP - conveniently expressed as the P:O2 ratio. P:O2 ratios, originally (‘classically’) inferred from thermal studies, have been considerably reduced over the past several decades by re-analysis of the stoichiometric coefficients separating sequential steps in the electron transport system – in particular, dropping the requirement that the coefficients have integer values. Since the early classical values are incompatible with the more recent estimates, we have constructed a simple, thermodynamically-constrained, algebraic model with which to re-investigate the resulting discrepancy. Our analysis fails to reconcile recent and classical estimates of P:O2 ratios; hence, we are left with a conundrum.